Tryptase plays a role in solid tumor angiogenesis and cell proliferation - Mathew, Anisha; Naithani, Manisha; Sehrawat, Amit; Sundriyal, Deepak; Shilpa, Pulturu Venkata; Nath, Uttam Kumar (International Journal of Advances in Medicine, 2020)
Tryptase, a serine protease released during mast cell degranulation has been associated with anaphylactic reactions and inflammations. In recent studies on solid tumor proliferation, it has been seen that tryptase has a role in tumor angiogenesis and tumor cell proliferation. This also makes tryptase a potential therapeutic target. Many anti-tryptase agents have shown to decrease tumor angiogenesis and proliferation. Authors have thus reviewed various articles which have done extensive studies on the role of tryptase as an important factor in tumor proliferation and angiogenesis.